Case Study of Economic Growth with the Act of Monopoly on Food Control in the Field of Poultry Farming from Upstream to Downstream by PT. Charoen Pokphand Indonesia Tbk - Indra Rahayu (Jurnal Syntax Transformation, 2024)
This study discusses economic growth, that economic growth does not only provide positive impacts but also negative impacts such as the existence of monopoly crimes that grow because unfair competition practices are based on tight business competition because they are required to increase profits as much as possible. The company PT. Charoen Pokphand Indonesia Tbk (CPIN) is indicated to have committed a monopoly violation in controlling food in the poultry sector in its business activities. The purpose of this study is that the government is expected to be truly present in trying, and anticipating, and or overcoming crimes in the field of monopoly practices and unfair business competition. Namely in overcoming the practice of controlling products from upstream to downstream, the authority in this case is the Business Competition Supervisory Commission (KPPU). This research method uses Normative Juridical analysis using secondary data with primary materials in the form of laws and expert opinions. The results of this study are that Business actors must implement Law No. 5 of 1999 Regarding Their Business Activities, and also the Business Competition Supervisory Commission (KPPU) must take a legal approach to PT Charoen Pokphand Indonesia (CPIN). In this study it can be concluded that all independent farmers are in a very weak position. Because they do not have a bargaining position against suppliers who supply input components such as seeds, feed and medicine, and do not have bargaining power from the sales side, because the market is controlled by poultry integrators such as in this study PT. CPIN. So that monopoly practices occur in product control from upstream to downstream.